Endoscopic ultrasound‐guided fine‐needle aspirate‐derived preclinical pancreatic cancer models reveal panitumumab sensitivity in KRAS wild‐type tumors. Issue 10 (28th February 2017) - Berry, William; Algar, Elizabeth; Kumar, Beena; Desmond, Christopher; Swan, Michael; Jenkins, Brendan J.; Croagh, Daniel
Abstract : Pancreatic cancer (PC) is largely refractory to existing therapies used in unselected patient trials, thus emphasizing the pressing need for new approaches for patient selection in personalized medicine. KRAS mutations occur in 90% of PC patients and confer resistance to epidermal growth factor receptor (EGFR) inhibitors ( e.g ., panitumumab), suggesting that KRAS wild‐type PC patients may benefit from targeted panitumumab therapy. Here, we use tumor tissue procured by endoscopic ultrasound‐guided fine‐needle aspirate (EUS‐FNA) to compare the in vivo sensitivity in patient‐derived xenografts (PDXs) of KRAS wild‐type and mutant PC tumors to panitumumab, and to profile the molecular signature of these tumors in patients with metastatic or localized disease. Specifically, RNASeq of EUS‐FNA‐derived tumor RNA from localized ( n  = 20) and metastatic ( n  = 20) PC cases revealed a comparable transcriptome profile. Screening the KRAS mutation status of tumor genomic DNA obtained from EUS‐FNAs stratified PC patients into either KRAS wild‐type or mutant cohorts, and the engraftment of representative KRAS wild‐type and mutant EUS‐FNA tumor samples into NOD/SCID mice revealed that the growth of KRAS wild‐type, but not mutant, PDXs was selectively suppressed with panitumumab. Furthermore, in silico transcriptome interrogation of The Cancer Genome Atlas (TCGA)‐derived KRAS wild‐type ( n  = 38) and mutant ( n  = 132) PC tumors revealed 391 differentially expressed genes. Taken together, our study validates EUS‐FNA for the application of a novel translational pipeline comprising KRAS mutation screening and PDXs, applicable to all PC patients, to evaluate personalized anti‐EGFR therapy in patients with KRAS wild‐type tumors. Abstract : What's new? While pancreatic cancer is a genetically heterogeneous disease, 90% of patients exhibit mutations in KRAS . Most patients also respond poorly to generalized treatments, suggesting that patient outcomes may depend on genetic profiling and personalized therapeutic approaches. A potential role for those approaches was explored here, using tumor tissue procured from patients via endoscopic ultrasound‐guided fine‐needle aspirate (EUS‐FNA). Patient‐derived xenografts were developed and screened for KRAS mutation status and sensitivity to panitumumab. Only KRAS wild‐type EUS‐FNA patient‐derived xenografts were sensitive to the drug. Genetic profiling coupled with EUS‐FNA, an existing clinical tool, is suited for rapid translation into clinical trials.